2022
DOI: 10.3390/foods11244105
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of the Yeast Wickerhamomyces anomalus to Hydrolyze Immunogenic Wheat Gliadin Proteins

Abstract: Gliadins proteins make up around 30% of total wheat flour proteins. They are involved in many immune disorders affecting an increasing number of people who eat foods made with wheat flour. The triggering factor is the accumulation in the gut of immunogenic peptides derived from incomplete degradation of gliadins by gastric proteases. Previous research has revealed the effectiveness of sourdough-fermentation technology or related lactic acid bacteria in reducing wheat flour allergenic proteins. However, there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
2
1
0
Order By: Relevance
“…This was also consistent with a recent study, showing that whey protein increased the viscosity of the dough and the strength of the expanded cells, thereby improving the gas retention rate during baking and resulting in a better specific volume [24]. In addition, it has been suggested that yeast strains have the ability to effectively utilize non-sugar-based substrates, assimilating and degrading amino acids in the dough to obtain carbon and nitrogen units [25]. Therefore, WOP may be used as a nitrogen source for yeast, which improves their gas production capacity.…”
Section: Specific Volume Of Bread Rollssupporting
confidence: 91%
“…This was also consistent with a recent study, showing that whey protein increased the viscosity of the dough and the strength of the expanded cells, thereby improving the gas retention rate during baking and resulting in a better specific volume [24]. In addition, it has been suggested that yeast strains have the ability to effectively utilize non-sugar-based substrates, assimilating and degrading amino acids in the dough to obtain carbon and nitrogen units [25]. Therefore, WOP may be used as a nitrogen source for yeast, which improves their gas production capacity.…”
Section: Specific Volume Of Bread Rollssupporting
confidence: 91%
“…The immunogenic reaction of gluten and gliadin proteins was shown in the range of 25-50 kDa. This aspect was accompanied with the study of [33]. Consistent with the results of SDS-PAGE, the immunogenic proteins related to α/β-gliadins were markedly decomposed by B. amyloliquefaciens subsp.…”
Section: The Presence Of Immunogenic Proteinsupporting
confidence: 73%
“…The presence of immunogenic proteins was verified using Western blotting with an anti-gliadin antibody (Figure 5), which reacts specifically with the deaminated peptide (KLQPFPQPELPYPQPQ), comprising the 33 mer sequence part of the wheat gliadin (residues 56-88) [33]. The immunogenic reaction of gluten and gliadin proteins was shown in the range of 25-50 kDa.…”
Section: The Presence Of Immunogenic Proteinmentioning
confidence: 97%